(untitled) (Al-Qamar, 2021)
This research analysis the religious and mystic symbols in the works of women fiction writers of Pakistan. Complete works of sixteen women fiction writers of Pakistan was studied for this research and it was tried to explore that how religion and Sufism are a source of symbols and metaphors in their novels and short stories. It has also been tried to determine in this research that whether the religious and mystic metaphors are used in their prevalent form or is there any change in their connotation. Findings show that there are innumerable mystic and religious metaphors in the works of these women fiction writers. Especially the texts by Bano Qudsia, Khalida Hussain and Jamila Hashmi are studded with religious and mystic metaphors.